GAMELAN DEGUNG SEBAGAI SARANA PENGIRING PROSESI TARI PANGBAGEA PADA WISUDA KE XVI STSI BANDUNG TAHUN 2012 - Kari Mulyana (Paraguna, 2018)
An  idea   of   karawitan   cultivation  in   gamelan  degung  is   the  realization  of imagination    and   expression   of   the   soul   based    on   the   experience   of   a cultivator/ stylist who is  applied  to a  claim.  In  this case the gamelan gamelan is functioned  as   an   accompaniment  of  the  "Pangbagea"  dance procession at  the opening ceremony of the XVI graduation  at STSI  Bandung as a  form of respect for all who attended the event.